Prospects for Developing Cultural Diplomacy between the Republics of Uzbekistan and Kazakhstan (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2025)
In this article, author examines the prospects for developing cultural diplomacy between the Republic of Uzbekistan and the Republic of Kazakhstan within the broader context of regional cooperation in Central Asia. Drawing on theoretical approaches to cultural diplomacy and soft power, the study conceptualizes culture as a strategic instrument for enhancing mutual trust, societal connectivity, and long-term interstate partnership. The research employs qualitative methods, including comparative analysis, document analysis of bilateral agreements, and the examination of institutional frameworks governing cultural cooperation. The author also argues that Uzbek–Kazakh cultural diplomacy has evolved from symbolic exchanges toward more institutionalized and multidimensional cooperation, encompassing education, cultural heritage preservation, creative industries, tourism, and people-to-people contacts. Particular attention is paid to shared historical memory, linguistic and cultural proximity, and the role of state and non-state actors in promoting cross-border cultural initiatives. The study identifies key drivers of cultural diplomacy development, such as political rapprochement, regional integration dynamics, and the growing demand for inclusive and society-oriented diplomatic practices.